Respuesta :

Answer: y= -7

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

(3)(−4)=y−5

−12=y+−5

−12=y−5

Step 2: Flip the equation.

y−5=−12

Step 3: Add 5 to both sides.

y−5+5=−12+5

y=−7

[tex]\huge\text{Hey there!}[/tex]

[tex]\large\textsf{3x = y - 5}\\\\\large\textsf{3(-4) = y - 5}\\\\\large\textsf{3(-4) = \boxed{\bf -12}}\\\\\large\textsf{-12 = y - 5}\\\\\large\textsf{TURN the EQUATION}\\\\\large\textsf{y - 5 = 12}\\\\\large\textsf{ADD 5 to BOTH SIDES}\\\\\large\textsf{y - 5 + 5 = -12 + 5}\\\\\large\textsf{CANCEL out: -5 + 5 because that gives you 0}\\\large\textsf{KEEP: -12 + 5 because that gives you the y-value}\\\\\large\textsf{y = -12 + 5}\\\\\large\textsf{-12 + 5 =\boxed{\bf -7}}[/tex]

[tex]\boxed{\boxed{\large\textsf{Answer: \huge \bf y = -7}}}\huge\checkmark[/tex]

[tex]\large\text{Good luck on your assignment and enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]